“Eu não quero ser julgada, quero ser tratada como uma ser humana”: sofrimento ético-político de travestis e mulheres transexuais que tiveram seus corpos deformados pelo silicone industrial - Dias, Guilherme José Parisi (2024)
Faced with the lack of psychosocial research about the effects of the clandestine use of industrial liquid of the silicone (ILS), the goal of this essay was to understand, by the light of the concept of ethic-politic suffering, the experience of the transvestites and the transgender women that had their bodies warped by the ILS. For such, three transvestites and a transgender woman were interviewed in São Paulo city, that were recruited by the group of the Ambulatory of integral health for transvestites and transsexual (CRT DST / Aids) and by a group of research that often works with this population. The qualitative data from the interviews were organized through the thematic analysis of content, that resulted in the following categories: a) “Justifications for use”, that synthesize the motivations for the use of the product: the charge coming from friends and the admiration by the bodies conquered with the ILS, the promise (not always achieved) to the more successful in the sex market, the access in definitive and immediate results, and inaccessible surgical protheses. b) “Time bomb”, in what the attributed senses are presented by the participants to their warped bodies: is now considered a time bomb, always faced with the possibility of an imminent and unpredictable problem, now is presented as a producer of personal satisfaction, as it is feminine, even if is warped; for most of them, the body can’t be hidden, but for one of the participants is. c) “Sex market and sexual love relationship”, in what the participants show that the egress of the sex market didn’t have direct relation with the effects of the ISL, situation that differs of the compulsory expulsion related by other researches and, also, reveals that the participants didn’t relate significant changes in the love sexual relationships after suffering deleterious effects of the ILS. d) “Daily life”, compared to before and after of the ISL use and that were related some undeniable changes in the participants’ daily life, including the search of remedial solutions. e) “Ethic-politic suffering”, that demonstrated the constellation of affections that follow the life path of the participants: regret, fear, loneliness, frustration, resignation, small happiness and personal satisfaction; and, also, the experience that opens wide the ethic-politic suffering of the participants. This takes place not only from the pain and the deformation, but for the lack of dignity, for being recognized and treated as people. At long last, the concept of the ethic-politic suffering showed to the relevance of the problematic, as it comes of a phenomenon mediated by inequalities and social injustices